The Analysis Factors Influencing the Implementation of Digital Social Entrepreneurship Application in Learning Engineering Education Using Structural Equation Modelling - Ganefri, -; Nordin, Norazah Mohd; Yulastri, Asmar; Hidayat, Hendra (Society of Visual Informatics, 2024)
A big part of being an entrepreneur is keeping up with modern technological advancements. However, many factors can lead to the ambition to launch an online company. Digital social entrepreneurship methodology examines the effects of college students' entrepreneurial mindset, smartphone usage habits, and Locus of Control on their digital business intentions. This research is fundamental because it provides information to universities that they can use to evaluate their plans for a digital-based entrepreneurship learning model that will help them provide a good education. This study involved 428 respondents, and the data obtained from the respondents were examined using the application of structural equation modeling with a survey approach for this research, which looks at a small portion of the community and collects data through questionnaires. The primary data was examined using SmartPLS 4.0 software and structural equation modeling. This study found that having an entrepreneurial mindset, smartphone use, and locus of control exerts a substantial and meaningful impact on one's aspiration to become a digital entrepreneur. We wanted to find out how college students' thinking about being an entrepreneur affects their desire to become a digital entrepreneur, using smartphone usage habits and locus of control as influencing factors. To make someone who wants to become an entrepreneur, this research needs to measure Digital Entrepreneurial Intention appropriately in students who take Entrepreneurship courses.